Perceived problems with involvement in decision making about breast cancer treatment and care: A cross-sectional study. Issue 3 (March 2021) - Mackenzie, Lisa; Mansfield, Elise; Herrmann, Anne; Grady, Alice; Evans, Tiffany-Jane; Sanson-Fisher, Robert
Highlights: 17 % of breast cancer patients had problems with involvement in medical decisions. Elevated psychological distress associated with increased odds of these problems. 39 % had discordant preferred and perceived roles in an important treatment decision. No factors were associated with this decision making role discordance. Need to enable involvement in healthcare decisions beyond major treatment choices. Abstract: Objective: To examine perceived problems with involvement in medical decision making among people with breast cancer from various phases of the cancer care trajectory. Methods: Breast cancer outpatients (n = 663) from 13 treatment centres completed a survey of perceived involvement in treatment and care decisions in the last month, psychological distress, demographic and clinical factors. A subsample (n = 98) from three centres completed a follow-up survey on preferred and perceived treatment decision making roles. Results: Overall, 112 (17 %) of 663 respondents from 13 oncology centres had experienced problems with involvement in decision making about their treatment and care in the last month, and of these, 36 (32 %) reported an unmet need for help with this problem. Elevated psychological distress was associated with 5.7 times the odds of reporting this problem and 6.6 times the odds of reporting this unmet need in the last month. Among the follow-up subsample (n = 98), 39% (n = 38) reported discordance between preferred and perceived role in a major treatment decision. Psychological distress was not associated with this outcome. Conclusion: Psychological distress was significantly associated with recently experiencing problems with involvement in treatment and care decisions, but not with misalignment of preferred and perceived roles in prior major treatment decisions. Practice implications: There is a need to maintain support for patient involvement in healthcare decisions across the cancer care continuum.